2017
DOI: 10.1016/j.wjorl.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Results of pediatric endoscopic and endoscopically assisted tympanoplasty

Abstract: ObjectivesTo evaluate the success of pediatric endoscopic and endoscopically assisted transcanal cartilage inlay tympanoplasty.MethodsRetrospective review of single surgeon experience.ResultsDuring a 3 year period, 30 children underwent 31 endoscopic or endoscopically assisted transcanal tympanoplasties by the senior surgeon using tragal cartilage/perichondrial inlay grafts. There were 22 boys and 8 girls, ranging in age from 3.5 to 17 years (median 6 years). All tragal cartilage grafts (31/31; 100%) survived.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“… 13 Using this technique in a pediatric population, Karatas described a success rate of 91.4 % (53/58) 14 and Akyigit in 93.7 % (30/32), 15 while Isaacson obtained intact tympanic membrane in 55 % of the sample (17/31), microperforations in 32 % (10/31) and larger perforations in 13 % (4/31). 16 In the present study, the identification of any perforation at the end of the postoperative follow-up was considered as an unsuccessful operation, regardless of the size and its association with the graft.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… 13 Using this technique in a pediatric population, Karatas described a success rate of 91.4 % (53/58) 14 and Akyigit in 93.7 % (30/32), 15 while Isaacson obtained intact tympanic membrane in 55 % of the sample (17/31), microperforations in 32 % (10/31) and larger perforations in 13 % (4/31). 16 In the present study, the identification of any perforation at the end of the postoperative follow-up was considered as an unsuccessful operation, regardless of the size and its association with the graft.…”
Section: Discussionmentioning
confidence: 96%
“…The cartilage graft donor site, the tragus, has low morbidity and shows better cosmetic results. 14 , 16 In the literature, the success rates of inlay cartilage tympanoplasty do not differ from the underlay techniques. 3 , 9 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…The number of subjects collected for meta‐analysis was 1004, including 513 patients belonging to EES and 491 patients under MES, and the included studies were published between 2015 and 2017. Nineteen studies were analyzed qualitatively, which were all case series studies, except for one retrospective cohort study (Table ) . The included studies were published between 1995 and 2017, and a total of 406 patients were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…James (6) looked at the outcomes of 250 pediatric patients and found an overall closure rate of 88%, again with no difference between the TEES and MT groups. Multiple studies that look at both pediatric and adult patients have found similar closure rates between 72 and 97% (7–12), with no differences between TEES and MT.…”
Section: Discussionmentioning
confidence: 96%